Bridging Gaps and Building Futures: Establishing initial teacher education for Asian languages in Ireland - Chang Zhang; Karen Ruddock (Teanga: The Journal of the Irish Association for Applied Linguistics)
This paper explores challenges and approaches associated with establishing initial teacher education for Asian languages in Ireland. This study identifies educational needs in the context of initial teacher education pathways through a three-year research project. It highlights the diversity in student cohorts, the demand for plurilingual and pluricultural awareness, and the need for alignment of teaching methodologies that would be effective in the Irish school context. Furthermore, it addresses the critical shortage of qualified teachers and makes recommendations for developing sustainable teacher supply chains. By analysing feedback from pre-service and in-service teachers, educational institutions, and policy frameworks, the paper aims to contribute to a discussion that would enhance the quality of and accessibility to Asian language education in Irish schools, ensuring it meets evolving educational and societal needs.